Sektor Pertanian untuk Pertumbuhan Ekonomi Regional Lampung - Ambya Ambya; Fitriani Fitriani; Intan Andya Bellapama; Muhammad Zaini (Politeknik Negeri Lampung, 2021)
Agricultural sector is a major contributor in the economic structure of Lampung. More than 44,75% people work in agricultural sector. However, the productivity of the agricultural sector was lower than other economic sectors. This study was conducted to analyze the development of agricultural sector based on the condition of the output, added value, and supply contribution basis. Method of cross-tabulation analysis was conducted on Input Output Table Lampung in 2010. The results of the analysis showed that the agricultural sector in Lampung province was still dominant in the economic structure of the region. But attention to the downward trend that occurred in each sub-sector needs to be paid because stagnation and slowing growth rate will be higher. Output contributions of agricultural sector were dominated by food crops, fisheries, plantation, and livestock. Meanwhile, the greatest added value contributor were primary agricultural sector and the food industry in the downstream (agroindustry). However, no sectors that have the largest distribution in Lampung are directly related to agriculture.